The Role of Apparatus Competence, Community Participation and Control Systems on Village Fund Financial Accountability - Pasolo, Fahrudin; Kooh, Ricky Phylemon; Zakaria, Zakaria; Sonjaya, Yaya (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This study is associative research, which aims to analyze, identify and explain the role of apparatus compe-tency, community participation and control systems on financial accountability of village funds in Mam-beramo Raya Regency. The amount of data used in the research was 84 respondents or 70.00% of the total population is 120 consisting of village officials, community leaders and stakeholders in the Greater Mam-beramo Regency environment, with a sampling technique using the Simple Random Sampling type Proba-bility Sampling technique. The main data source for this research was obtained through distributing ques-tionnaires to all respondents. The statistical method used to test the hypothesis is multiple linear regression analysis using SPSS. Based on partial and simultaneous test results, it was found that apparatus, community participation and control systems had a positive and significant effect on financial accountability of village funds in Mamberamo Raya Regency. This study not only highlights the dynamics within the Mamberamo Raya District Government but also the efforts of the Greater Mamberamo District Government to increase efficiency, transparency and accountability in managing village funds, as well as improving the perfor-mance of village officials.